On the Structure of Consciousness: Experiential Swaths within Holism - Bloch, Shir (Stance: an international undergraduate philosophy journal, 2022)
Some views of holism fail to fully encapsulate the structure and independence of consciousness while others are reductionist in their insistence on a strict structure. After examining holism and mental state consciousness, I move to my own proposal for the structure of consciousness: experiential swaths. By highlighting the phenomenal interdependence of some aspects of consciousness without conceding that all aspects are so strongly intertwined, experiential swaths allow for further conceptual structurization within consciousness.